Peranan Pendidikan Islam di Era Millenial - Anita Pronika (Medan Resource Center, 2022)
The role of Islamic education in the current era of globalization is facing big challenges, especially if it is associated with its contribution to the formation of modern civilization and culture that is relevant to the development of science and technology (IPTEK). Today humans live in the millennial era. This era which is a continuation of the global era has created new challenges that must be turned into opportunities that can be utilized as well as possible, so that these challenges bring blessings to everyone who does it. Because the millennial era, apart from having similarities, also has differences, especially in the use of digital technology that goes beyond the computer era, Islamic education with various types and levels, ranging from traditional boarding schools that are non-formal in nature, to modern boarding schools with various programs, ranging from Kindergarten to Kindergarten. from childhood to tertiary institutions, are institutionally part of the national education system. With such a position, Islamic education inevitably has to contribute, even be responsible for preparing humans to face the millennial era. Namely humans who are able to turn challenges into opportunities, and can take advantage of them for their material and spiritual welfare.